Unusual Presentations of Birth Related Cervical Spinal Cord Injury - Lee, Chien-Chung; Chou, I-Jun; Chang, Yi-Jung; Chiang, Ming-Chou (Frontiers in Pediatrics, 2020)
Neonatal spinal cord injury is a rare complication of birth trauma by difficult delivery. The typical manifestations are often catastrophic, include decreased or absent movement, loss of reflexes, apnea or periodic breathing, and a lack of response to painful stimulation. The outcome is usually fatal or severe, with long-term sequelae of respiratory insufficiency, limb weakness, or even paralysis of the limbs. We described a male neonate with a C2 spinal cord injury who was born smoothly by vaginal delivery and was unnoticed initially due to unusual subtle symptoms. He presented with a hoarse voice, swallowing dysfunction, decreased movement of upper limbs, and hypercapnia. After receiving corticosteroid therapy and rehabilitation, he recovered much except that he still needed ventilator support at night.